Day and night surgery: is there any influence in the patient postoperative period of urgent colorectal intervention? - Fernandes, S (2016)
BACKGROUND: Medical activity performed outside regular work hours may increase risk for patients and professionals. There is few data with respect to urgent colorectal surgery. The aim of this work was to evaluate the impact of daytime versus nighttime surgery on postoperative period of patients with acute colorectal disease. METHODS: A retrospective study was conducted in a sample of patients with acute colorectal disease who underwent urgent surgery at the General Surgery Unit of Braga Hospital, between January 2005 and March 2013. Patients were stratified by operative time of day into a daytime group (surgery between 8:00 and 20:59) and the nighttime group (21:00-7:59) and compared for clinical and surgical parameters. A questionnaire was distributed to surgeons, covering aspects related to the practice of urgent colorectal surgery and fatigue. RESULTS: A total of 330 patients were included, with 214 (64.8%) in the daytime group and 116 (35.2%) in the nighttime group. Colorectal cancer was the most frequent pathology. Waiting time (p < 0.001) and total length of hospital stay (p = 0.008) were significantly longer in the daytime group. There were no significant differences with respect to early or late complications. However, 100% of surgeons reported that they are less proficient during nighttime. CONCLUSIONS: Among patients with acute colorectal disease subjected to urgent surgery, there was no significant association between nighttime surgery and the presence of postoperative medical and surgical morbidities. Patients who were subjected to daytime surgery had longer length of stay at the hospital.